Écritures confinées : raconter la marche au temps du confinement. Les pratiques langagières au prisme de l’expérientiel et du psychédélique - Luca Greco (Itinéraires)
Working on a corpus composed of images and texts collected in two digital spaces, in Italian and in French, I will question the political and the poetic potential as it is at work in the “writings during the lockdown”: texts produced at the time of the first lockdown, in Italy and in France, in which walking is both the source of the writing activity and the object of the narrative. Because of their capacity to go beyond spatio-temporal boundaries, to insert themselves into multisemiotic assemblages, and to question their solely textual and informational dimension, I will call these texts “excessive” and analyze their different degrees of excess. The focus on the irreducibly experiential and psychedelic, even excessive, dimension of these texts will allow me, by way of conclusion, to make some proposals for a sociolinguistics that is attentive to the experiential and psychedelic dimension of language practices.